1995
DOI: 10.1111/j.1349-7006.1995.tb02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection, Serum Pepsinogen Level and Gastric Cancer: A Case‐Control Study in Japan

Abstract: We conducted a case‐control study to evaluate the effect of Helicobacter pylori (HP) infection on the risk of gastric cancer in Tokyo, Japan. The sera at the time of diagnosis from 282 gastric cancer cases and 767 sex‐ and age‐matched cancer‐free controls were tested for the presence of anti‐HP IgG antibody (HM‐CAP ELISA kit) and serum pepsinogen (PG) level (PG I and PG II Riabead). No significant association was observed in all sets [matched odds ratio (OR)=1.04, 95% confidence interval: 0.73–1.49]. In subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 28 publications
5
68
0
Order By: Relevance
“…We did not obtain information at base line on Helicobacter pylori infection (HP). Among Japanese, HP infection significantly increases the risk of stomach cancer (Blaser et al, 1993;Fukuda et al, 1995;Kikuchi et al, 1995;Watanabe et al, 1997). However, a previous prospective cohort study showed that HP infection significantly increased the risk of stomach cancer in males (RR=2.59, 95% CI=1.03 -6.50) but not in females (RR=0.99, 95% CI=0.36 -2.68) (Yamagata et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We did not obtain information at base line on Helicobacter pylori infection (HP). Among Japanese, HP infection significantly increases the risk of stomach cancer (Blaser et al, 1993;Fukuda et al, 1995;Kikuchi et al, 1995;Watanabe et al, 1997). However, a previous prospective cohort study showed that HP infection significantly increased the risk of stomach cancer in males (RR=2.59, 95% CI=1.03 -6.50) but not in females (RR=0.99, 95% CI=0.36 -2.68) (Yamagata et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with a short follow-up period were also found among the older patients in the H. pylori-negative group. Fukuda et al [28] suggested that H. pylori had already been eradicated in an older population with primary gastric cancer at the time of operation. Although we did not examine H. pylori prevalence before the operation, our data is in line with their observation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15) Such a trend could be explained by a decrease in H. pylori prevalence among those who were born later due to the steadily improving sanitary conditions.…”
Section: Discussionmentioning
confidence: 99%